2022
DOI: 10.1002/edm2.381
|View full text |Cite
|
Sign up to set email alerts
|

The DAPA‐DIET study: Metabolic response to Dapagliflozin combined with dietary carbohydrate restriction in patients with Type 2 Diabetes Mellitus and Obesity—A longitudinal cohort study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A study of 24-week empagliflozin treatment with nutritional education showed significant decreases in body weight and improvement in blood glucose level without postprandial hunger sensation in the empagliflozin-treated group compared with the placebo group [ 30 ]. A 12-month observational study of dapagliflozin in combination with dietary carbohydrate restriction and intervention by specialist weight-management dietitians throughout the study period showed decreases in body weight and blood leptin level but no changes in appetite in patients with obesity and type 2 diabetes [ 31 ]. Taken together, previous research suggests that administration of oral SGLT2i combined with nutritional education may be an effective treatment that suppresses appetite.…”
Section: Discussionmentioning
confidence: 99%
“…A study of 24-week empagliflozin treatment with nutritional education showed significant decreases in body weight and improvement in blood glucose level without postprandial hunger sensation in the empagliflozin-treated group compared with the placebo group [ 30 ]. A 12-month observational study of dapagliflozin in combination with dietary carbohydrate restriction and intervention by specialist weight-management dietitians throughout the study period showed decreases in body weight and blood leptin level but no changes in appetite in patients with obesity and type 2 diabetes [ 31 ]. Taken together, previous research suggests that administration of oral SGLT2i combined with nutritional education may be an effective treatment that suppresses appetite.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest are also results of a human study. In the DAPA-DIET study, a 12-month cohort study in a secondary care setting, Hanson et al ( 15 ) explored the effect of dapagliflozin combined with an LCD on weight loss, energy expenditure and appetite in patients with T2DM and obesity. The authors found that the combination therapy of SGLT2i and LCD led to significant and substantial weight loss, and reduced serum leptin levels in study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the combination therapy of SGLT2i and LCD led to significant and substantial weight loss, and reduced serum leptin levels in study participants. Intriguingly, Hanson et al ( 15 ) suggested that the LCD intervention may curb carbohydrate cravings often associated with SGLT2i therapy, which may help to optimise sustainable weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…The DAPA-DIET study, evaluating dapagliflozin's impact on body weight in obese and diabetic patients, which has demonstrated a mean body fat mass loss of 9.9 kg over 12 months, but it has to be said that participants were on a diet with a limited amount of carbohydrates. Moreover, after 12 months of treatment, there was a significant reduction of mean serum leptin [66].…”
Section: Flozins and The Body Massmentioning
confidence: 91%